Long-Term Outlook of Energy Use and CO2 Emissions from Transport in Central and Eastern Europe - Zachariadis, Theodoros; Kouvaritakis, Nikos (My University, 2003)
A forecast of transport activity, energy consumption and carbon dioxide emissions from transportation, carried out under ‘business as usual’ economic assumptions, is presented for the 10 countries of Central and Eastern Europe that have acquired the status of ‘accession countries’ to the European Union. Energy demand is projected under considerations of the dynamic evolution of transport modes and their use, the evolution of automotive fuel prices, which are assumed to gradually converge with Western European price levels within the current decade, and assumptions on efficiency improvements in all transport modes according to current technological trends and European regulations. The results, showing transportation energy demand to double and CO2 emissions to be 70% higher in 2030 compared to 2000, are compared with other published forecasts and discussed with a view to potential future energy and environmental impacts in these countries, outlining major policy implications.
Keywords: Energy efficiency; Forecast; Mobility; Transportation